2019
DOI: 10.1096/fj.201900099r
|View full text |Cite
|
Sign up to set email alerts
|

Leukemic IL‐17RB signaling regulates leukemic survival and chemoresistance

Abstract: Secreted proteins provide crucial signals that have been implicated in the development of acute myeloid leukemia (AML) in the bone marrow microenvironment. Here we identify aberrant expressions of inflammatory IL‐17B and its receptor (IL‐17RB) in human and mouse mixed lineage leukemia–rearranged AML cells, which were further increased after exposure to chemotherapy. Interestingly, silencing of IL‐17B or IL‐17RB led to significant suppression of leukemic cell survival and disease progression in vivo. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
(66 reference statements)
2
5
0
Order By: Relevance
“…Similar results were recently obtained in leukemic cells by Guo et al, who demonstrated that the IL-17RB pathway promotes the survival of MOLM-13 AML cells by increasing ERK and NF-KB phosphorylation and Bcl-2 level and consequently, resistance to the purine analog Ara-C, the frontline chemotherapeutic agent for AML (38). Importantly, in each study, inhibition of the IL-17B/IL-17RB axis by downregulating receptor expression in tumor cells or by using neutralizing anti-IL-17RB antibodies restored chemosensitivity in vitro (28,38) and in vivo (10). Similarly, IL-17B or IL-17RB silencing in cancer cells or treatment with antibodies targeting IL-17RB reduced proliferation of MDA-MB361 breast cancer cells and MOLM-13 AML cells in vitro and tumor growth in vivo in xenograft models based on these cell lines (28,38).…”
Section: Mechanisms Of Actionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similar results were recently obtained in leukemic cells by Guo et al, who demonstrated that the IL-17RB pathway promotes the survival of MOLM-13 AML cells by increasing ERK and NF-KB phosphorylation and Bcl-2 level and consequently, resistance to the purine analog Ara-C, the frontline chemotherapeutic agent for AML (38). Importantly, in each study, inhibition of the IL-17B/IL-17RB axis by downregulating receptor expression in tumor cells or by using neutralizing anti-IL-17RB antibodies restored chemosensitivity in vitro (28,38) and in vivo (10). Similarly, IL-17B or IL-17RB silencing in cancer cells or treatment with antibodies targeting IL-17RB reduced proliferation of MDA-MB361 breast cancer cells and MOLM-13 AML cells in vitro and tumor growth in vivo in xenograft models based on these cell lines (28,38).…”
Section: Mechanisms Of Actionsupporting
confidence: 88%
“…This leads to resistance to chemotherapeutic drugs, such as etoposide (a topoisomerase II inhibitor) (28), and paclitaxel (a spindle poison) (10). Similar results were recently obtained in leukemic cells by Guo et al, who demonstrated that the IL-17RB pathway promotes the survival of MOLM-13 AML cells by increasing ERK and NF-KB phosphorylation and Bcl-2 level and consequently, resistance to the purine analog Ara-C, the frontline chemotherapeutic agent for AML (38). Importantly, in each study, inhibition of the IL-17B/IL-17RB axis by downregulating receptor expression in tumor cells or by using neutralizing anti-IL-17RB antibodies restored chemosensitivity in vitro (28,38) and in vivo (10).…”
Section: Mechanisms Of Actionsupporting
confidence: 60%
See 2 more Smart Citations
“…In vivo, anti-IL-17RB monoclonal antibodies inhibited tumor metastasis and prolonged survival in a mouse xenograft model (171). Others confirmed a direct tumor-promoting activity of IL-17B in gastric cancer (172), thyroid cancer (173), and in acute myeloid leukemia (174).…”
Section: Pro-tumor Activities Of Il-17b Il-17c and Il-17fmentioning
confidence: 95%